Bluetooth 5.0 Modem Design for IoT Devices - Mohamed, Khaled Salah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides an introduction to Bluetooth technology, with a specific focus on developing a hardware architecture for its modem. The major concepts and techniques involved in Bluetooth technology are discussed, with special emphasis on hardware mapping. The book starts simply to allow the reader to master quickly the basic concepts, before addressing the advanced features. This book differs from existing content in that it presents Bluetooth Transceiver architecture suitable for implementation in an FPGA for IoT Devices. It will examine several digital algorithms for modulation and demodulation of Bluetooth signals, locking on the carrier phase, and synchronizing the symbol. Many of these previously analog designs have been translated to the digital domain. Presents Bluetooth Transceiver architecture suitable for implementation in an FPGA; Includes comparative study between different architectures; Discusses the tradeoff between cost and performance when a Bluetooth transceiver is designed using non-data aided techniques for clock and timing recovery.
Introduction to Bluetooth -- GFSK Modem Design -- DPSK Modem Design -- Verification of the Bluetooth modem -- Conclusions.
Keywords: Electronic circuits; Telecommunication; Electronic Circuits and Systems; Communications Engineering, Networks; Microwaves, RF Engineering and Optical Communications; Bluetooth technology; Internet of things; Modems